Coatings To Retard The Formation Of Tarnish On Silver And Silver Alloys. - J J. McEwan; M Scott (The Southern African Institute of Mining and Metallurgy, 2006)
Silver and silver alloys tarnish readily by the formation of tarnish on the surface when exposed to a wide range of sulphur-containing atmospheres. This tarnish is unsightly and undesirable and can be removed either with a silver polish or a chemical dip. Polishes are, however, not suitable for irregular and embossed surfaces such as on coins, medallions and jewellery items, because of uneven removal of the tarnish layer and excessive wear. Successful tarnish protection can be achieved by either storing the items away from the aggressive atmosphere or by coating/treating the exposed surfaces with a protective layer. Storage is feasible for collections but is not suitable for items that are handled or worn regularly, such as jewellery. A number of commercial coatings and treatments have been developed, but to date there has not been a systematic evaluation of tarnish protection. This paper details the performance of a range of generic coatings in an accelerated tarnish test. The degree of tarnish was evaluated by means of loss in reflectivity and change in colour. Four coatings/treatments improved the tarnish resistance of silver by more than tenfold. These include an organic lacquer, rhodium electroplating and an organic self-assembled monolayer (SAM) conversion coating. Research is continuing to optimise these coatings. Keywords: silver alloys, tarnish resistant coatings, silver polishes.